Entrepreneurial career success from a Chinese perspective: conceptualization, operationalization, and validation - Lau, Victor P; Shaffer, Margaret A; Au, Kevin (Journal of International Business Studies, 2007)
We conducted a series of studies to conceptualize, operationalize, and validate entrepreneurial career success from a Chinese perspective. For Study 1, we defined constructs based on interpretations of Hong Kong entrepreneurs. In Study 2 (Hong Kong entrepreneurs) and Study 3 (Shanghai entrepreneurs and their employees), we developed and validated measures. Guided primarily by social identity theory, we mapped the criterion space and tested etic and emic predictors of career success.